2017
DOI: 10.1103/physrevb.96.214205
|View full text |Cite
|
Sign up to set email alerts
|

Multifractal metal in a disordered Josephson junctions array

Abstract: We report the results of the numerical study of the non-dissipative quantum Josephson junction chain with the focus on the statistics of many-body wave functions and local energy spectra. The disorder in this chain is due to the random offset charges. This chain is one of the simplest physical systems to study many-body localization. We show that the system may exhibit three distinct regimes: insulating, characterized by the full localization of many-body wavefunctions, fully delocalized (metallic) one charact… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
52
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 48 publications
1
52
0
Order By: Relevance
“…Energy spectrum of the kinetic part of the Hamiltonian is limited to the stripe E ∈ (−N Γ, +N Γ). For the energies E = N outside of this band (that is, | | > Γ) the Green function can be found from (14) by the Laplace transform and further saddle-point integration (using N 1 condition):…”
Section: Matrix Elements: Analytic Derivation and Numerical Resultsmentioning
confidence: 99%
“…Energy spectrum of the kinetic part of the Hamiltonian is limited to the stripe E ∈ (−N Γ, +N Γ). For the energies E = N outside of this band (that is, | | > Γ) the Green function can be found from (14) by the Laplace transform and further saddle-point integration (using N 1 condition):…”
Section: Matrix Elements: Analytic Derivation and Numerical Resultsmentioning
confidence: 99%
“…The most interesting property of the RP model is the existence of a finite region of non-ergodic extended states. Such a region appears at the metallic side of the many-body localization transition in an array of Josephson junctions [23,24,25,26,27]. This nonergodic behaviour has also been analyzed in other quantum systems [28,29,30,31,32] and it has been suggested that it can play an important role for quantum information [33].…”
Section: Introductionmentioning
confidence: 99%
“…Multifractal statistics appears at the Anderson localization transition for single-particle lattice systems [17,[65][66][67][68][69][70][71]. In addition, recent examples have reported (multi)fractal phases extend-ing over a whole range of parameters [72][73][74][75][76][77][78][79][80][81][82][83][84][85][86]. Multifractal wavefunctions have been found for some quantum maps [68,70,87,88].…”
Section: Introductionmentioning
confidence: 99%